PENGARUH METODE PROJECT BASED LEARNING VERSUS METODE PROBLEM BASED LEARNING DAN MOTIVASI TERHADAP PRESTASI BELAJAR AGAMA KRISTEN PADA SISWA SD NEGERI AUSE DISTRIK WAPOGA - Syultje Sihasale; Sabariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the differences in effectiveness between Project-Based Learning (PjBL) and Problem-Based Learning (PBL) and examine the influence of learning motivation on the achievement of Christian Religious Education in Ause Elementary School students, Wapoga District. The research design used a quantitative approach with a quasi-experiment. All participants were divided into two treatment groups: one taught using PjBL, the other using PBL. The main instruments were an achievement test to measure cognitive achievement and a motivation questionnaire that captures intrinsic-extrinsic aspects. Data were collected through observation, questionnaire distribution, and test administration, then analyzed using SPSS 27 with Two-Way ANOVA. The analysis results show that the learning method variable has a significant impact on achievement (F=162.695; Sig.=0.000): PjBL students obtained higher scores than PBL. Motivation also had a significant effect (F=64.094; Sig.=0.000); highly motivated students achieved better results. Furthermore, there was a significant interaction between method and motivation (F=46.466; Sig.=0.000), indicating that the effectiveness of the method increases when supported by high learning motivation. In other words, both PjBL and PBL will work optimally if students have a strong learning drive. The conclusion confirms that Christian Religious Education achievement is significantly determined by the type of method, the level of motivation, and the synergy between the two. Teachers are advised to integrate strategies that require active participation—such as projects or problem-solving—while designing activities that strengthen intrinsic motivation and provide extrinsic reinforcement. This integrated approach is believed to improve both learning outcomes and student independence. These findings are relevant for similar schools in remote areas facing limited resources but demanding future improvements in the quality of learning.